Development of a formative peer observation protocol for STEM faculty reflection. Issue 3 (2nd April 2020) - Dillon, Heather; James, Carolyn; Prestholdt, Tara; Peterson, Valerie; Salomone, Stephanie; Anctil, Eric
Abstract: Faculty peer observation has seen increasing uptake in recent years, in some cases as an alternative or supplement to student teaching evaluations. While many universities encourage faculty peer observation, it is not widely used in a formal way for formative assessment. This article outlines the development of a new faculty peer observation protocol designed for formative assessment of evidence-based educational practices. The goal of the protocol is to foster reflective teaching practices. The peer observation protocol has been designed to mitigate common faculty fears of classroom observation, with detailed assessment methods for specific topic areas. Preliminary testing of the protocol at one university indicated positive faculty outcomes with regard to personal reflection: all the faculty who tested the protocol reported that the observation process had been helpful for them to reflect on their teaching.